2006
DOI: 10.1016/j.tcm.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Inflammation on Endothelium-Dependent Vasodilation

Abstract: The importance of inflammation in the pathogenesis of atherosclerosis is well established. The vascular endothelium contributes to and is affected by the inflammatory process. For example, a variety of cytokines have the ability to "activate" the endothelium and thereby promote expression of adhesion molecules and chemotactic factors that accelerate the inflammatory process and direct accumulation of leukocytes to specific sites in the arterial tree. In experimental systems, activation of endothelial cells is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 42 publications
(39 reference statements)
0
89
1
1
Order By: Relevance
“…The endothelium regulates vascular tone, thrombosis, local inflammation, composition of the vascular wall, and angiogenesis by producing a variety of paracrine factors [1][2][3][4]. For example, the endothelium controls vascular tone by producing vasoconstrictors such as endothelin-1 and angiotensin 2 and vasodilators such as prostacyclin, endothelium-derived hyperpolarizing factor, and nitric oxide.…”
Section: Introduction Endothelial Regulation Of Vascular Homeostasismentioning
confidence: 99%
“…The endothelium regulates vascular tone, thrombosis, local inflammation, composition of the vascular wall, and angiogenesis by producing a variety of paracrine factors [1][2][3][4]. For example, the endothelium controls vascular tone by producing vasoconstrictors such as endothelin-1 and angiotensin 2 and vasodilators such as prostacyclin, endothelium-derived hyperpolarizing factor, and nitric oxide.…”
Section: Introduction Endothelial Regulation Of Vascular Homeostasismentioning
confidence: 99%
“…When the body temperature begins to rise above the normal range, heat-dissipating behaviors, such as sweating and vasodilation, are initiated (44,45). Vasodilation, which is already heightened in the inflammatory state (46,47), allows for increased blood flow to all organs, including the skin. Yosipovitch et al (48) showed that skin blood flow correlates strongly with forearm skin temperature, with increased blood flow resulting in higher skin temperature.…”
mentioning
confidence: 99%
“…With arrival of improved chromophores, MSOT could enable the interrogation of a wider range of processes and functions offering pathophysiological readings of disease that may affect the FMD response [25]. The results of the current study testified the possible utility of MSOT over ultrasonography for FMD measurements.…”
Section: Resultsmentioning
confidence: 62%